MODELING THE PROCESS OF DEBT MANAGEMENT IN THE SYSTEM OF ADMINISTRATION OF FINANCIAL ACTIVITIES OF THE ENTERPRISE - Sablina, N.; Lytovchenko, O. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers topical aspects of managing receivables and payables of the enterprise as a prerequisite for improving payment discipline. The essence of debt management in the system of administration of financial activity of the enterprise, the economic nature of receivables and payables, the advantages and disadvantages of the formation of receivables and payables of the enterprise are studied. Part of the receivables and payables in the financial and economic activities of the enterprise is inevitable and must be within acceptable limits, respectively, not to cause financial risks that may cause bankruptcy. The article emphasizes the need for rational and sound management of receivables and payables, as it has a direct impact on the effective functioning and development of the enterprise, the level of its financial results and image among partner companies. The reasons for the formation and impact on the activities of enterprises receivables and payables are outlined. Factors influencing the amount of accounts payable are considered. The main tasks of receivables and payables management of the enterprise are researched and formulated. The system of measures for management of receivables and payables of the enterprise is investigated and generalized. the company needs to form a certain model of business process management. In order to increase the efficiency of receivables and payables management at enterprises, a structural and functional model of the company's receivables and payables management process has been developed. The conceptual directions of improving the management of receivables and payables are given and the need to strengthen the practical component of the proposed recommendations is emphasized.